Micro- and Macroscale Patterns of Petal Morphogenesis in Nigella damascena (Ranunculaceae) Revealed by Geometric Morphometrics and Cellular Analyses - Galipot, Pierre; Gerber, Sylvain; Le Guilloux, Martine; Jabbour, Florian; Damerval, Catherine (Frontiers in Plant Science, 2021)
Petals, the inner organs in a differentiated perianth, generally play an important role in pollinator attraction. As such, they exhibit an extraordinary diversity of shapes, sizes and colors. Being involved in pollinator attraction and reward, they are privileged targets of evolution. The corolla of the Ranunculaceae species Nigella damascena consists of elaborate nectariferous petals, made of a stalk, upper and lower lips forming a nectar pouch, shiny pseudo-nectaries, and pilose ears. While the main events of petal development are properly described, little is known about the pattern of organ size and shape covariation and the cellular dynamics during development. Here, we investigate the relationships between morphogenesis and growth of N. damascena petal using geometric morphometrics coupled with the study of cell characteristics. First, we found that petal shape and size dynamics are allometric during development, and that their covariation suggests that petal shape change dynamics are exponentially slower than growth. We then found that cell proliferation is the major driver of shape patterning during development, while petal size dynamics are mostly driven by cell expansion. Our analyses provide a quantitative basis to characterize the relationships among shape, size and cell characteristics during the development of an elaborate floral structure. Such studies lay ground for future evo-devo investigations of the large morphological diversity observed in nectariferous structures, in Ranunculaceae and beyond.